Reproductive toxicology of environmental endocrine-disrupting chemicals in women: a cohort study protocol - Zhang, Shuyi; Gao, Fumei; Fu, Min; Zhang, Qiuxiang; Guan, Jing; Shen, Huan (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Epidemiological evidence over the last few decades has consistently shown that exposure to endocrine-disrupting chemicals (EDCs) is associated with adverse reproductive health outcomes, including male and female infertility, poor-pregnancy outcomes, and increased risk of diseases in childhood and beyond. To investigate the effects of EDCs and lifestyle on all aspects of reproduction (including early oocyte development, fertilization, embryo development, embryo implantation, abortion, and preterm birth). Methods: We performed this cohort study on patients receiving in vitro fertilization (IVF) treatment. Biological samples including urine, serum, follicular fluid, semen, fetal tissue, decidua, and placenta, were obtained. Results: By studying the correlations between reproductive outcomes and environmental pollutant exposure and lifestyle, we determined the toxicological mechanisms and health effects of EDCs on female reproductive health. We found that higher concentrations of per- and polyfluoroalkyl substances were correlated with polycystic ovary syndrome (PCOS). Using specific biomarkers, we also detected the concentrations of organophosphorus flame retardants (OPFRs) in urine and found that OPFRs may disrupt hormone homeostasis. Discussion: All of these results reveal EDCs may disrupt female reproduction.